Management Strategy for Accelerating Long School Expectations and Average Length of Schooling in West Java - Sutarman Sutarman (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2025)
This study aims to examine efforts to accelerate the Expected Years of Schooling (EYS) and the Mean Years of Schooling (MYS) in West Java. The region continues to face significant educational challenges, including disparities in teacher distribution and quality, inconsistencies in institutional management, inadequate educational infrastructure, and limited access to education particularly in rural areas. These issues hinder the progress toward achieving targeted levels of EYS and MYS. Employing a qualitative approach through a case study method, data collection was conducted using triangulation techniques involving observations, interviews, and document analysis. The findings highlight strategies designed to enhance the pace of educational attainment in West Java. These strategies involve coordinated efforts between the Provincial Education Office, the Regional Office of the Ministry of Religious Affairs, and Higher Education Service Institutions. Despite the integration of planning, implementation, monitoring, and evaluation processes, and the allocation of various funding sources such as Central and Regional School Operational Assistance, as well as the Indonesia Smart Card progress remains below expectations due to persistent structural and systemic barriers.